Ontology of Language and Culture in Philosophy of Name by A. F. Losev - O. Yu. Astakhov; O. V. Rtishcheva (Концепт: философия, религия, культура, 2025)
The relevance of the study is due to the necessity to analyze mutual determination of the development of language and culture so as to expand the problematic field of humanities.  Thus, the article is focused on Alexei Losev’s book Philosophy of Name (1927) characterized with a kind of polyphony that calls for bridging the author’s position with a variety of philosophical trends dealing with the ontological problems of language and culture. The article’s authors set the goal of examining the specifics of studies on ontological characteristics of language through the prism of its cultural representation, analysing Losev’s conceptual framework. In this regard the authors set the following tasks: firstly, to determine the pre-object structure of the name as a mythologeme, by highlighting the primary status of the advancement from the internal sense, related to the existential foundations of life, to its external representations; secondly, to analyze the reverse motion from essence to its appearances as realized in the word expressing the fullness of individual and cultural meanings. In accordance with the set tasks, the results of the study follow the general logic of Losev’s conceptualizations. The dialectic of Losev’s reasoning combines the appraisal of the ascent to the Absolute in understanding the name, on the one hand, with the significance of the descent to the word with its agile lively content, on the other. Losev integrates these two trends in language development through myth, which he sees as a living reality—an actual manifestation of essence fixed in a name. The conclusions are indicated by appealing to the ontological Pan-Unity allowing Losev to integrate the ideas of man and the world, to connect reality to thought in the context of universal relations the wholeness of which becomes real in the living space of culture.